Pre-hypertension and hypertension in college students in Kuwait: A neglected issue - Hana T Al-Majed; Ali A Sadek (Wolters Kluwer Medknow Publications, 2012)
Objective: To determine the proportion of pre-hypertension and hypertension in college students in Kuwait and their related risk factors. Materials and Methods: A total of 803, randomly selected students aged 17 to 23 years (346 male, 457 female) from different colleges in Kuwait, were included in the study between 2009 and 2010. Systolic and diastolic blood pressure measurements were taken by trained personnel. Pre-hypertension was defined as systolic pressure between 120 and 139 mm Hg or diastolic pressure between 80 and 89 mm Hg. Risk factor measurements that were determined, included smoking, body mass index (BMI), and family history of hypertension. Blood samples were collected and impaired glucose tolerance (IGT) and lipid profile levels were determined. Results: There were no hypotensive students. Normotensives constituted 53.5% (n = 430), pre-hypertensives formed 39.5% (n = 317), and hypertensive students comprised of 7% (n = 56). The overall proportions of hypertension and pre-hypertension were higher among male students (85.7 and 64.4%) than female students (14.3 and 35.6%), respectively. Hypertensive and pre-hypertensive students versus normotensive students had significantly higher levels of BMI-based obesity, smoking, glycated hemoglobin (HbA1c), and IGT. Also, hypertensive and pre-hypertensive, compared to normotensive students, had significantly higher proportions (21.4, 18.3, and 4.0%, respectively) of risky high-density lipoprotein (HDL) level (< 1 mg / dL), cholesterol (7.1, 3.8, and 1.4%, respectively), and triglycerides (TG) (17.9, 9.1, and 7.9%, respectively) where p was< 0.001, 0.016, and 0.051, respectively. Conclusion: Hypertensive and pre-hypertensive students showed elevated levels of lipids and BMI-based obesity more than normotensive students. TG, HDL, HbA1c, and cholesterol appeared to influence pre-hypertension.